Management of apposing, full‐thickness tracheal perforations in two horses. (12th September 2015) - Gillen, A.; Munsterman, A.; Pinto, N.; Caldwell, F.; Wooldridge, A.; Cuming, R.; Hanson, R.
Summary Two horses, one 15‐year‐old Arabian gelding and one 10‐year‐old Quarter Horse gelding, presented with a history of marked subcutaneous emphysema. The first case exhibited no external wound, although there was a depression noted on the ventral neck. The second case had a laceration on the ventral aspect of the neck over the trachea. Endoscopic examination revealed both horses to have concurrent dorsal and ventral perforations of the trachea. The horses were managed by placing a short, cuffed, J‐shaped tracheostomy tube in the ventral perforation, while the dorsal perforation healed. The dorsal perforation in the first horse was allowed to heal by second intention, whereas sutures were placed in the dorsal perforation in the second case to reduce the healing time. Both horses were maintained on oral antimicrobial and nonsteroidal anti‐inflammatory medications throughout treatment. The dorsal perforation healed after 13 days in the first horse, and 22 days in the second horse. The ventral perforation healed in both horses by second intention following tracheostomy removal, giving a cosmetically acceptable result. In addition to facilitating tracheal healing, the tracheostomy tubes prevented the progression of subcutaneous emphysema, and promoted its resolution.